Graphicacy as a form of communication in the primary school - Wilmot, Pamela Dianne (Rhodes University, Faculty of Education, Department of Education, 1998)
Children of today inhabit a multi-dimensional world, and in order to communicate effectively in it, they need the ability to utilise four forms of communication namely, oracy, literacy, numeracy and graphicacy. Communicating in graphic form requires an ability to both encode and decode spatial information using symbols, which requires the utilisation and application of spatial perceptual skills and concepts. The acquisition of graphic skills has been influenced by traditional developmental perspectives; increasingly the assumptions underpinning these have been challenged by more recent international research findings. The draft Curriculum Framework for General and Further Education and Training (1996: 18) identifies graphic literacy as one of the critical outcomes of the new South African curriculum. For graphic literacy to be an achievable outcome of the new curriculum, we need to investigate the skills and concepts underpinning this form of communication. The goal of this research is to investigate graphicacy as a form of communication in South African primary schools. However, given the scope of a research project of this nature, it was decided that rather than dealing with graphicacy per se, pictures as the most frequent and concrete type of graphic communication encountered by young learners would be focused on. In seeking to investigate pictures, the first stage of the study is concerned with diagnosing and illuminating children's graphic skill development through identifying: what skills they use; how they use and apply these when communicating through and interpreting symbols; and the difficulties they experience when, firstly, encoding spatial information through a series of practical and drawing tasks; and secondly, when reading and interpreting pictures. The second stage of the study investigates the extent to which children's early childhood experiences may or may not have impeded or enhanced the acquisition of skills necessary for understanding and communicating about space. The research findings, evaluated according to existing and emerging theoretical perspectives on graphicacy, will help to illuminate the current situation regarding the graphic literacy of South African primary school children. The study may contribute to wider international debates about graphicacy as a form of communication and the development of graphic literacy, from a South African perspective.
Keywords: School children -- South Africa; Visual communication; Perception in children; Visual literacy; Pictures